New categories of spare parts and their impact on the increase of insurance crime in automobile insurance - Lewicki, Wojciech; Stankiewicz, Bogusław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The introduction in 2003 of ‘sectoral exemptions’ in the automotive industry was vital for the economic policies of the European Union by providing consumers with easy access to goods and services for the automotive market, and maximally similar prices. Before the introduction of the regulation, they were required to assemble and sell spare parts only signed by the manufactures cars, calling them original parts. Regulation defined the term ‘original parts’ and ‘alternative parts’ as the elements installed in the car to its components, which are necessary for the proper functioning of the vehicle. Although few years has already passed since the GVO regulations has been introduced, the analysis of the components of the compensations paid out still shows that prices of the spare parts that are included in the general amounts of the repairs’ costs of the cars and which are reimbursed by the insurance companies is significant. The issue of the spare parts choice within the process of the motor loss adjustment still are a big research problem especially considering the increase of the crime committed in the field of the automobile insurance in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 130-139
Keywords: insurance market; insurance fraud; motor market; spare parts; sectoral exemptions; rynek ubezpieczeniowy; przestępstwo ubezpieczeniowe; rynek motoryzacyjny; części zamienne; wyłączenia sektorowe